172k views
3 votes
Without using log, Solve for x.


27^(1-x) =(1)/(9^(2x) )

User Belladonna
by
5.5k points

1 Answer

2 votes

ANSWER


x = - 3

Step-by-step explanation

The given equation is


27^(1-x) =(1)/(9^(2x) )

Recall that


\frac{1}{ {a}^(m) } = {a}^( - m)

Apply this rule on the right hand side to get,


27^(1-x) =9^( - 2x)

Express both sides to base 3.


3^(3(1-x)) =3^(2( - 2x))

Equate the exponents:

3(1-x)=2(-2x)

Expand:


3 - 3x = - 4x

Group like terms,


4x - 3x = - 3


x = - 3

User Manuel Salvadores
by
5.9k points